Медіамова у проєкції лінгвопраксеологічної перспективи - Василенко, В. А.; Vasylenko, V. A.; Валентина Василенко (Закарпатські філологічні студії. - 2021. - Вип. 17, т. 2. - С. 116-120, 2021)
Розглянуто лінгвопраксіологічний вектор аналізу сучасної медіалінгвістики. Показано, що для лінгвопраксіологіі центральними стають екстралінгвістичні чинники професійної поведінки, що дає змогу встановити правила ефективного використання мови в професійному мовленні, пояснити формування тих чи інших мовних проявів. Окреслено, що крізь призму праксеологічного підходу предметом вивчення медіалінгвістики стає мовна системність медіатекстів різних типів, формально-смислова структура яких створюється поєднанням і взаємодією як мовних, так і немовних компонентів, не лише внутрітекстових, а й міжтекстових чинників. Зазначено, що у мовній структурі будь-якого висловлювання закладаються можливості попередження читацького «опору» когнітивному і емоційно-вольовому впливу з боку суб'єкта мовлення – без цього ефективний вплив на масову аудиторію неможливий. Виявлено, що поряд зі спрямованістю цих досліджень на вивчення закономірностей функціонування мови в різних ситуаціях професійного медійного спілкування їх відрізняє інтерес до опису правил ефективної професійної мовної поведінки, а це дає змогу широко використовувати типологічний метод, разом із тим встановлювати критерії ефективності окремих мовних дій або їх сукупностей у професійній мовній поведінці в медіасередовищі.

The linguistic-praxeological vector of analysis is considered as perspective for contemporary media linguistics in the article. The topmost features of this approach, such as its subject, key categories, and methods of analysis are reflected in the survey. It is noted that the differentiation of linguistics on the basis of its subject (that is the sphere of language functioning) demonstrates the heuristic results. Whereas scientists reveal the specifics of language usage in different areas, they learn more about the forms and ways of effective language use in speech. It is shown that extra linguistic factors of professional behavior become central for linguistic-praxeology. This allows establishing the rules of effective language usage in professional speech, to explain the formation of certain language manifestations. It is outlined in the research that the subject of media linguistics study becomes the linguistic system of media texts of different types through the prism of praxeological approach. It should be mentioned that the formalsemantic structure of these media texts is created by combining and interacting both linguistic and non-linguistic components, as well as intratextual and intertextual factors. In the linguistic-praxeological approach the mass media researcher deals with the actual language units that are often analyzed as part of the structure of the whole text. It is noted that there are certain opportunities to prevent the reader's "resistance" to cognitive and emotional influence from the part of the speech subject in the language structure of any statement. Effective influence on the mass audience is impossible without this phenomenon. It was also found that along with the focus of these surveys to study the patterns of language in different situations of professional media communication, they are interested in describing the rules of effective professional language behavior. Therefore this provides widespread usage of the typological method while establishing criteria for effectiveness of individual language actions or aggregates in professional language behavior in the media environment. The own semantic vision of development necessity of recommendations and warnings concerning the organization of effective language activity and creation of effective models of certain work directions is formed in the research.

Рассмотрен лингвопраксиологический вектор анализа современной медиалингвистики. Показано, что для лингвопраксиологии центральными становятся экстралингвистические факторы профессионального поведения, что позволяет установить правила эффективного использования языка в профессиональной речи, объяснить формирование тех или иных языковых проявлений. Определено, что сквозь призму праксеологического подхода предметом изучения медиалингвистики становится языковая системность медиатекстов разных типов, формально-смысловая структура которых создается сочетанием и взаимодействием как языковых, так и неречевых компонентов, не только внутритекстовых, но и межтекстовых факторов. Отмечено, что в языковой структуре любого высказывания закладываются возможности предупреждения читательского «сопротивления» когнитивному и эмоционально-волевому влиянию со стороны субъекта речи – без этого эффективное влияние на массовую аудиторию невозможно. Выявлено, что наряду с направленностью этих исследований на изучение закономерностей функционирования языка в различных ситуациях профессионального медийного общения их отличает интерес к описанию правил эффективного профессионального языкового поведения, что позволяет широко использовать типологический метод, вместе с тем устанавливать критерии эффективности отдельных языковых действий или их совокупностей в профессиональном языковом поведении в медиасреде.
Media language in the projection of linguistic-praxeological perspective
Keywords: Мова. Мовознавство. Літературознавство. Language. Linguistics. History and Criticism of Literature. Язык. Языкознание. Литературоведение; Наукові публікації. Scientific publications. Научные публикации; лінгвопраксіологія; linguopraxiology; лингвопраксиология; медіалінгвістіка; media linguistics; медиалингвистика; ефективна мовна діяльність; effective language activity; эффективная речевая деятельность; медійне спілкування; media communication; медийное общение; медіамова; media language; медиаязык; медіатекст; media text; медиатекст